2020
DOI: 10.4103/tcmj.tcmj_215_19
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of peak lactate during cardiopulmonary bypass in adult cardiac surgeries: A retrospective cohort study

Abstract: Objective: Tissue hypoperfusion during cardiopulmonary bypass (CPB) affects cardiac surgical outcomes. Lactate, an end product of anaerobic glycolysis from oxygen deficit, is a marker of tissue hypoxia. In this study, we aimed to identify the prognostic value of blood lactate level during CPB in predicting outcomes in adults undergoing cardiac surgeries. Materials and Methods: We retrospectively reviewed the medical records of patients who underwent cardiac surgeries wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 20 publications
0
2
1
Order By: Relevance
“…26,32 High peak lactate levels during CPB are also known to be associated with high mortality. 36 In our study, no statistically significant differences were found between the two patient groups in terms of MAEs or mortality. However, Group S had a greater need for ECMOs, longer ventilation times, and longer ICU stays.…”
Section: Discussioncontrasting
confidence: 60%
“…26,32 High peak lactate levels during CPB are also known to be associated with high mortality. 36 In our study, no statistically significant differences were found between the two patient groups in terms of MAEs or mortality. However, Group S had a greater need for ECMOs, longer ventilation times, and longer ICU stays.…”
Section: Discussioncontrasting
confidence: 60%
“…27 The stress response to surgery, the use of beta-adrenergic agonists, systemic inflammation reaction, and lactate load from blood transfusion all contribute to elevated lactate levels in patients undergoing cardiac surgery. 28,29 Besides, end-organ hypoperfusion is not uncommon after cardiac surgery which might be a resource of lactic acidosis. And lactic acidosis also increases whole blood viscosity and hematocrit, leading to exacerbate hypoperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, the lactate and ketone ion levels contribute the most to elevation of AG 27 . The stress response to surgery, the use of beta‐adrenergic agonists, systemic inflammation reaction, and lactate load from blood transfusion all contribute to elevated lactate levels in patients undergoing cardiac surgery 28,29 . Besides, end‐organ hypoperfusion is not uncommon after cardiac surgery which might be a resource of lactic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…En particular, niveles de lactato que no se normalizan se han asociado con una tasa de mortalidad postoperatoria de aproximadamente el 20 % (5)(6)(7)(8).…”
Section: Introductionunclassified
“…La tasa de mortalidad a nivel mundial de los pacientes con hiperlactatemia tras cirugía cardiaca está estimada en 14%, pero varía significativamente en distintos lugares del mundo, como 3.1% en Marruecos, 5.6% en Colombia, el 14.4% en Taiwán, y el 14.9% en Australia. Por tal motivo, es importante mantener actualizada la información en nuestro país para poder correlacionarla con la información a nivel global (7,9,10) (8,(11)(12)(13)(14).…”
Section: Introductionunclassified